Banning incandescent light bulbs in the shadow of the EU Emissions Trading Scheme. (4th July 2017) - Perino, Grischa; Pioch, Thomas
Abstract : The light bulb ban introduced by the EU is used as an example to illustrate how to assess the climate impact of a policy that overlaps with a cap-and-trade scheme. The European Commission estimates that by 2020 the reduction in GHG emissions induced by banning incandescent light bulbs will reach 15 million tons annually. The number is a conservative estimate for the reduction in emissions from lighting if the total residential stock of incandescent light bulbs in 2008 is replaced by more efficient lighting sources. However, it ignores that use-phase and some non-use-phase emissions are covered by the EU Emission Trading Scheme (EU ETS). This drastically reduces the amount of GHG emissions saved. Policy relevance Several policies such as the EU-wide ban on incandescent light bulbs, energy efficiency mandates and support mechanisms for renewable energy overlap with the EU ETS. While there are typically several justifications for these policies, a chief reason is the reduction of GHG emissions. However, given that the aggregate emissions of the industries covered are fixed by the EU ETS, the climate change mitigation aspect of these policies is not obvious. Using the light bulb ban as an example, this article illustrates how a focus on non-EU ETS emissions changes the assessment of an intervention in terms of GHG reductions.